Доказать тождество: 1) cos2a/(sina*cosa+sin^2a)= ctga -1; 2) (sin2a-2cosa)/sina-sin^2a)=...

0 голосов
462 просмотров

Доказать тождество:
1) cos2a/(sina*cosa+sin^2a)= ctga -1;
2) (sin2a-2cosa)/sina-sin^2a)= -2ctga;
3) tga(1+cos2a)=sin2a;
4) ((1-cos2a+sin2a)/(cos2a+sin2a))*ctga=1;


Алгебра (146 баллов) | 462 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

1
cos2a/(sina*cosa+sin^2a)= ctga -1
(cos²a-sin²a)/[sina(cosa+sina)=(cosa-sina)(cosa+sina)/[sina(cosa+sina)=
=(cosa-sina)/sina=cosa/sina-sina/sina=ctga-1
2
(sin2a-2cosa)/sina-sin^2a)= -2ctga
(2sinacosa-2cosa)/[sina(1-sina)]=2cosa(sina-1)/[sina(1-sina)]=
=-2cosa/sina=-2ctga
3
tga(1+cos2a)=sin2a
tga*2cos²a=sina*2cos²a/cosa=2sinacosa=sin2a


(750k баллов)